Factors Related to the Level of Patient Adherence in Taking Hypertensive Medication at RSU Imelda Pekerja Indonesia Medan in 2022 - Dame, Arta Marisi; Roslinda, Rada (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
This article describes the factors related to the level of patient adherence in taking hypertension medication at RSU Imelda Pekerja Indonesia Medan. This study used quantitative methods with an analytical survey approach and the research design used in this study was Cross Sectional. The sample in this study was 35 people. The results of statistical test analysis using the Chi-Sguare statistical test where the results showed meaningful relationships for age variables (p value = 0.005), for sex variables (p value = 0.557), for knowledge variables (p value = 0.011), for officer role variables (p value = 0.007) and for family support variables (p value = 0.012).